Pengaruh Motivasi Terhadap Kinerja Karyawan (Studi Kasus Pada Bank Swasta di Kota Tegal) - Subroto, Setyowati; ., Gunistiyo (SOSEKHUM, 2009)
The aims of this research is to know the effect of achievement motivation, affiliate motivation and motivastion in command to employees performance and know the motivation variable giving biggest influence to employees performance. Pursuant to result analyse, known that by partial achievement motivation variable have positive and significant influence to employees performance. By partial motivation to affiliate variable have positive and significant influence to employees performance. By partial also motivation in command variable have positive and significant influence to employees permance. Result of calculation known that by there are significant influence by simultan form variable achievement motivation, motivation to affiliate and motivation in command to employees performance. Pursuant to comparison asses the elasticity of coefficient regression known the value of regression elasticity coefficient achievement motivation variable have biggest compared to other variable. Its means achievement motivation variable have biggest influence to employees performance compared to other variable, so that acceptable fourth hypothesis. Keyword : Motivation, Employees Performance.